Distribution of Recognition Times to Fruity Flavor of Gummy Candies in Healthy Adults. (August 2018) - Miyaoka, Satomi; Iwamori, Hajime; Miyaoka, Yozo
Times for recognition of fruity flavors in six gummy candies were measured using an electromyography-based system in 23 young healthy participants. They were instructed to chew one of the gummy candies at a random order and to press a button as soon as possible when they recognized what flavor was. The measured 181 recognition times showed two distributions, normally ( n  = 107) and non-normally ( n  = 74). The overall average of the normal distribution was 7.5 seconds (±2.34 seconds; standard deviation ), and there were no differences in the average ratios among the gummy candies. Eighteen of the participants reported 41 inconsistent reports with flavors that were provided by the manufacturer. The most frequently observed report was an apple-flavored gummy candy (14, 34.1%) mainly for a pear-flavored. However, there was no significant correlation between the numbers of recognition times and those of inconsistent flavors among the used gummy candies.